A Cross-Sectional Study to Assess Causes of Undernutrition in Under 5year Children in Gwalior District: A Population Based Study - Bhatia, Manohar; Mishra, Ashok; SasmitaMungi3 (National Journal of Community Medicine, 2014)
Background: India has the largest burden of child mortality and undernutrition in the world. More than one-third of the world's 150 million undernourished children younger than 5yr old live in India. This study was conducted with objectives to identify possible causative factors for under-nutrition; to identify prevalent nutrition practices for sick children; and to assess the perception of respondents towards Govt. programs and Govt. health services for improving the nutrition of children. Material &Methods: This cross-sectional study was conducted in Gwalior District among doctors, Supporting Staff (Anganwadi workers, ANM and Feeding Demonstrators) and Mothers using a pre-designed, pre-tested, semi-structured questionnaire. Results: Total 82% Doctors believed that lack of awareness about nutritional requirements of young children, 78% supporting staff believed Faulty feeding habits and 71.66% mothers believed that low quality of health care were the most important cause of child undernutrition. Majority of mothers said that being too busy with household and other work was the most important reason for their inability to give best care to their under five children. Majority of mothers were dissatisfied with the quality of Anganwadi services. Conclusion: Study clearly indicates that there are still miles to go in dealing with the problem of undernutrition. Empowering mother, improving Anganwadi services and most importantly spreading knowledge and awareness about child rearing practices can help in solving the problem of undernutrition.